Identification of mouse CD4+ T cell epitopes in SARS-CoV-2 BA.1 spike and nucleocapsid for use in peptide:MHCII tetramers - Bricio-Moreno, Laura; Barreto de Albuquerque, Juliana; Neary, Jake M.; Nguyen, Thao; Kuhn, Lucy F.; Yeung, YeePui; Hastie, Kathryn M.; Landeras-Bueno, Sara; Olmedillas, Eduardo; Hariharan, Chitra; Nathan, Anusha; Getz, Matthew A.; et al. (Frontiers in Immunology, 2024)
Understanding adaptive immunity against SARS-CoV-2 is a major requisite for the development of effective vaccines and treatments for COVID-19. CD4+ T cells play an integral role in this process primarily by generating antiviral cytokines and providing help to antibody-producing B cells. To empower detailed studies of SARS-CoV-2-specific CD4+ T cell responses in mouse models, we comprehensively mapped I-Ab-restricted epitopes for the spike and nucleocapsid proteins of the BA.1 variant of concern via IFNg ELISpot assay. This was followed by the generation of corresponding peptide:MHCII tetramer reagents to directly stain epitope-specific T cells. Using this rigorous validation strategy, we identified 6 immunogenic epitopes in spike and 3 in nucleocapsid, all of which are conserved in the ancestral Wuhan strain. We also validated a previously identified epitope from Wuhan that is absent in BA.1. These epitopes and tetramers will be invaluable tools for SARS-CoV-2 antigen-specific CD4+ T cell studies in mice.